The Church Struggle and the Confessing Church: An Introduction to Bonhoeffer's Context - Hockenos, Matthew D. (Studies in Christian-Jewish Relations, 2011)
This article traces the German church struggle form 1933 to 1945 with particular emphasis on Dietrich Bonhoeffer’s role. Although Bonhoeffer’s status in the world today is that of a great theologian and courageous opponent of the Nazi regime, he did not have much of an impact on the direction of the Confessing Church during the church struggle. Bonhoeffer’s striking albeit marginal role in the German church struggle and his inability to affect significantly the direction of the Confessing Church was due to many factors, including his young age, his liberal-democratic politics, his absence from Germany from October 1933 to April 1935, his vacillating and at times contradictory positions on central issues, his radical theological critique of the Nazi state, his friendship with and family ties to Christians of Jewish descent, and ultimately his willingness to risk his life to destroy Hitler’s regime.